Dampak Stabilitas Keuangan Daerah terhadap Ketahanan Keuangan Pemerintah Daerah - Harahap, Muhammad Nasim; Dailibas, Dailibas; Nasution, Raden; Chaerudin, Chaerudin; Muslihat, Asep (STIE Indonesia Banking School, 2023)
This research investigates the impact of local financial stability on the financial resilience of local governments. The study examines the relationship between financial stability, efficient budget management, wise debt control, long-term financial sustainability, and the financial resilience of local governments. The research employs a quantitative approach, utilizing regression analysis to analyze the data collected from various local governments. The findings indicate a significant positive influence of financial stability, efficient budget management, wise debt control, and long-term financial sustainability on the financial resilience of local governments. The study contributes to the understanding of the crucial factors affecting the financial well-being of local governments and provides insights for policymakers to enhance financial planning and resilience.